Correlation between Vaginal Cytology, Serum Progesterone and Oestradiol-17b in Captive Sumatran Rhinoceros (Dicerorhinus Sumatrensis) - Choong, Siew Shean (2002)
Vaginal cytology was conducted in 4 females for 121 to 204 days, and 328 vaginal smears were examined. Vaginal flushing and aspiration were done to obtain vaginal cells, and then stained according to Modified Shorr's staining method. Blood samples were also collected for hormonal analysis, so as to be used as a guide in the determination of the different stages of oestrous cycle. Cellular morphology and staining properties were similar to those reported previously in bitches and cows. The percentage of cornified cells was found to be significantly different from other cell types on the day of oestrus. A total of 12 eosinophilic index (EI) peaks were recorded, averaged at 57.42±12.96%; with the highest at 88.17%, and the lowest at 49.10%. Twenty five percent of EI peaks observed were of second peaks, ranged between 49.06% and 65.00%, and occurred 13.33±2.08 days after the first peak. Length of oestrous cycle was 22±6.36 days based on vaginal cytology. From the serum progesterone (P4) profile, the recorded length of oestrous cycle was 2S±7.64 days. It was also noted that oestrous cycles were irregular and inconsistent during this study period, lag periods between two oestruses ranged between 21 and >100 days. The range of serum P4 concentration differed between individuals. The highest concentration recorded was 3.47 ng/mL in one individual; whereas the lowest peak recorded was only 1.34 ng/mL. However, the effect of such differences on the reproductive functions of these animals is yet to be determined. Correlation of EI with serum P4 profile was weak, with correlation coefficient, r, valued at -0.254. Nevertheless, correlation coefficient in one individual (R2) was higher, with r=-0.40S. This may be due to variations in the level of EI and progesterone concentrations among the animals and between oestrous cycles of an animal. Serum oestradiol-1713 (E2) profile was erratic and did not correlate significantly with either vaginal cytology or serum P4 profile. Wide range of serum E2 between individuals was also documented, with the highest and lowest values being 2S.00 pg/mL and 6.49 pg/mL respectively. Peaks of E2 occurred throughout the length of oestrous cycle indicated by serum P4 profile. This may be due to the low specificity and sensitivity of the commercial kit used towards oestradiol-1713 detection in the Sumatran rhinoceros. This study showed that there are reservations in the use of vaginal cytology for detection of oestrus in this species of animal.